SCINTIGRAPHIC EVALUATION OF GALLBLADDER EMPYTING IN DIABETIC PATIENTS - Ahmet AYDIN; Kamil KUMANLIOĞLU; Erkan DEREBEK; Enver AKALIN; Yusuf DUMAN; Yücel BATUR; Taylan KABALAK (Turkish Journal of Gastroenterology, 2020)
-